A Comprehensive Economic Analysis of Hospitalised Patients with Dengue Fever - Putro, Wahyu Gito; Media, Lintang; Ratnaningtyas, Tri Okta; Swanbamrung, Charuai; Riski, Zaki Maulana (Global Health Science Group, 2023)
DHF poses a significant public health concern in regions characterised by tropical and subtropical climates. Indonesia is among the nations that have encountered challenges in effectively addressing the issue of DHF, as seen by the escalating number of cases. West Java Province is positioned at the forefront among the top three provinces in terms of reporting the highest number of DHF cases, with a total of 10,722 cases. The number of DHF cases in Depok City shown a notable rise, escalating from 1,276 cases and resulting in 3 fatalities in the year 2020 to a total of 3,155 cases in the subsequent year of 2021. The primary aim of this study was to ascertain the demographic characteristics of families with inpatients and intensive care patients, and to assess the overall financial burden associated with treatment, non-treatment expenses, indirect costs, and economic losses experienced by families of inpatients and intensive care patients afflicted with DHF disease at Depok City Hospital. The present study employed a descriptive analytic strategy utilising a quantitative methodology. The study was carried out at the Depok City General Hospital, utilising both primary and secondary data sources. The population under investigation in this study had a total of 429 patients. The sample size for the study was determined to be 203 using Lameshow's sample size technique. The variables considered in this study encompassed demographic characteristics, the overall direct expenses associated with treatment, the entire direct costs associated with non-treatment, the aggregate indirect costs, and the complete economic losses experienced by families of patients with DHF at Depok City General Hospital. The data underwent analysed through the application of univariate analysis and cost evaluation computation. The findings indicated that the average direct cost of therapy was Rp. 7,797,833 or USD 507.23. The average non-treatment direct expenditures amount to Rp. 2,701,440 or USD 178.59. The average value of indirect costs was Rp. 2,471,557 or USD 163.40. The average family economic loss was Rp. 12,970,830 or USD 843.72. Conclusions: This study demonstrates that the sickness known as dengue hemorrhagic fever (DHF) can result in financial burdens for families, particularly in terms of non-medical direct costs and indirect costs.